From the Reticuloendothelial to Mononuclear Phagocyte System – The Unaccounted Years - Yona, Simon; Gordon, Siamon (Frontiers in Immunology, 2015)
It is over 125 years since Ilya Metchnikoff described the significance of phagocytosis. In this review we examine the early origins and development of macrophage research continuing after his death in 1916, through the period of the Reticulo-Endothelial System. Studies on these cells resulted in a substantial literature spanning immunology, haematology, biochemistry and pathology. Early histological studies on morphology and in situ labelling laid the foundations to appreciate the diversity and functional capacity of these cells in the steady state and during pathology. We complete this phagocyte retrospective with the establishment of the Mononuclear Phagocyte System nomenclature half a century ago.